Variation of Copper and Cadmium in Pelagic Plankton of Hamilton Harbour - Koenig, Brenda (My University, 1992)
Temporal variation in the levels of Cu and Cd in zooplankton, phytoplankton and water taken from five pelagic stations in Hamilton Harbour during three separate sampling periods (June, August and October/November 1990) was examined. Significant seasonal variation occurred in the Cu and Cd levels measured in water and phytoplankton (Cu Water: df=2, F=32.28, P≤.0001, Cu Phytoplankton: df=2, F=48.94, P≤.0001 and Cd Water: df=2, F=18.98, P≤.0001, Cd Phytoplankton: df=2, F=58.81, P≤.0001). However, the Cu levels observed in zooplankton did not vary significantly with season (df=2, F=1.79, P≤.1919). The maximal levels of Cd in zooplankton in November may be due to increased ingestion of material that is resuspended during turnover. Similarly, the peak levels of Cu and Cd recorded in November in phytoplankton may be due to a combination of processes: a) change in the size structure of the phytoplankton community to smaller individuals with higher metal sorption capacities and/or b) contamination of phytoplanktonic tissue samples by resuspended material. Phytoplankton metal levels (Cu and Cd) are negatively correlated with chl a concentrations (n=45, r=.8171, ≤.0001 and n-41, r=-.5961, P≤. 0001, respectively). These relationships are likely the result of a dilution effect. Zooplankton Cd levels were positively correlated with water and phytoplankton Cd concentrations (n=41, r=.3211, P≤.0407 and r=.7667, P≤.0001) while Cu levels were not correlated with any of the variables tested. The difference between the correlatedness of Cd levels in zooplankton to water and phytoplankton Cd levels compared to the lack of this type of relationship with regard to Cu may be attributable to the biological function of each metal in zooplankton. Cu is required in small amounts for physiological processes and may be regulated whereas Cd has no known biological function.
Variation of Cu and Cd in Plankton of Hamilton Harbour
Keywords: plankton; harbour; copper; cadmium